O conteúdo dietético dos ácidos graxos modifica parâmetros de memória em ratos: estudo comparativo entre uma dieta baseada no mediterrâneo versus dietas ocidentais - Haygert, Priscila Ferreira (2018)
Population aging associated with altered eating habits has been increasing the incidence of cognitive impairment and neurodegenerative diseases, including Alzheimer's disease (AD), which is a serious public health problem and accounts for about 70% of dementia in the elderly population. Thus, the preservation of brain function and the reduction of the risk of neurological disorders has become an important issue to improving quality of life. Recent studies have shown that the type of lifelong feeding may disadvantage individual susceptibility to the development of dementia. The ratio between the daily intake of food sources of polyunsaturated fatty acids (PUFAs) omega-3 (n-3) and omega-6 (n-6) have been linked to lower risks of many chronic diseases. However, chronic consumption of processed foods is increasing, rich in trans fatty acids (TFA), which can cause structural changes in membrane phospholipids, affecting brain neurotransmission. The high consumption of TFA has been related to several metabolic diseases, favoring also cerebral oxidative processes, which may be related to the development of neuropsychiatric diseases. In an attempt to minimize the damage caused by the consumption of TFA, this has been replaced by interesterified fat (IF), a plastic fat rich in saturated fatty acids (SFA), low or free trans configuration and still little known their actions on the CNS. The objective of this study was to evaluate the influence of the consumption of oils and fats on the Mediterranean diet versus Western diets, from weaning to adulthood, on memory loss per se, as well as on an animal model of cognitive deficit in male Wistar rats. For this, after the postnatal day (PND) 21, the animals were fed a standard diet supplemented with different oils or fats (20%), resulting in three different experimental groups: Mediterranean diet (MD, with an ideal ratio of PUFA (WD-1, with TFA (30%) or western diet 2 (WD-2, with IF (SFA-55%). After, the animals was subdivided to receive saline (control group) or scopolamine (ESCO) (1mg / kg ip), an inductor of cognitive deficit, and submitted to behavioral evaluations of memory. 24 h after the last behavioral, the animals were euthanized to remove plasma and hippocampus to evaluated the levels of pro inflammatory cytokines, IL-1β, IL-6, TNF-α in the plasma and IL-1β in the hippocampus, anti-inflammatory (IL-10) in the plasma, besides histological images in the hippocampus were evaluated. The results obtained showed that MD-fed animals presented better memory performance and lower levels of pro inflammatory cytokines, whereas WD-1 and WD-2 fed groups had impaired memory, which showed a positive correlation with plasma pro inflammatory cytokines, whose levels were increased. Experimental groups treated with ESCO presented increase memory damage, regardless of diet. Histological sections of the hippocampus showed that MD-fed animals had regular neuronal cells, while groups fed the western diets (WD-1 and WD-2) showed reduced and irregular neuronal layer. Taken together, it is possible suggest that the prevalence of different types of FA in the diet may facilitate the development of cognitive neurological disorders. Moreover, in our understanding, we are demonstrating for the first time that the replacement of TFA by IF in the Western diet does not represent benefits, considering neuropsychiatric diseases, and particularly, those that affect memory performance. Thus, it is possible to propose that fats recognized as "processed" are capable of exerting deleterious influences on memory parameters, since their chronic consumption was associated with increased levels of proinflammatory cytokines in the plasma and hippocampus, also altering the neuronal organization of the hippocampus.